Reconstruction of CNGS neutrino events in the emulsions of the OPERA experiment - Pozzato, Michele <1980> (Alma Mater Studiorum - Università di Bologna, 2009)
The OPERA experiment aims at the direct observation of ν_mu -> ν_tau oscillations in the CNGS (CERN Neutrinos to Gran Sasso) neutrino beam produced at CERN; since the ν_e contamination in the CNGS beam is low, OPERA will also be able to study the sub-dominant oscillation channel ν_mu -> ν_e.